EFFICACY OF ZINCODERM G CREAM AGAINST WOUND INFECTION BY METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS IN SPRAGUEDAWLEY RATS - SATYAM SM; BAIRY KL; MUSHARAF S; FERNANDES D; SHASHIDHAR V (International Journal of Pharma and Bio Sciences, 2015)
A fixed drug combinations (FDC) of clobetasol, gentamicin and Zinc namely Zincoderm G cream is available in the market. There are studies which shows the efficacy of each component in bacterial infections, but as FDC including Zinc has not been reported yet. A study was undertaken to evaluate the efficacy of Zincoderm G cream in burn wound infected with methicillin-resistant Staphylococcus aureus. Methods: A total of 18 Sprague-Dawley rats (male, pathogen free, 6-8 weeks old) were used in this study. The rats were divided into 3 groups of 6 rats each. 25-30 mg of test drugs (Zincoderm G cream with or without Zinc) was applied on S.aureus infected burn wound affected area of back of rats for two weeks. Degree of bacterial infection was assessed by quantification of bacteria. There was 30% mortality seen in both MRSA toxic control (cream base) and MRSA positive control (Zincoderm G cream without Zinc) groups. Only 10% mortality was observed in the MRSA group which was treated with Zincoderm G cream with Zinc. But, there was no significant difference found in MRSA bacterial concentration (number of CFU/ml wound fluid; after treatment) for both Zincoderm G with/without Zinc when compared with the MRSA toxic control (cream base) groupAddition of Zinc to Zincoderm G did not exhibit distinct killing profile against MRSA. We found that Zincoderm G cream with Zinc could not exhibit the distinct killing profiles against MRSA.